The effect of controlled release fertilizer and earthworm compost on Chamomile (Matricaria chamomilla L.) yield. (Revista Brasileira de Plantas Medicinais, 2000)
The experiments were carried out under greenhouse conditions at the State University, Londrina, PR, Brazil, between June and September 1999. Chamomile growth and yield were evaluated, using different ratios of controlled release fertilizer CRF (15-9-12) and earthworm compost (EC) produced from yard waste. Treatments were: T1) Control; T2) 6 kg.m-3 of CRF plus 2 kg.m-3 of EC; T3) 4 kg.m-3 of CRF plus 4 kg.m-3 of EC; T4) 2 kg.m-3 of CRF plus 6 kg.m-3 of EC; T5) 8 kg.m-3 of CRF. Yield, number, and diameter of flowers were evaluated at 12, 14, 16, 19, 21,23, 28, 30, 33, 42, 49, 55, 61, 67, 74, 81 days after transplantation. A “Split Plot in Time” complete randomized design was used with four replications. The experimental data were submitted to analysis of variance, “t” test, and the Tukey test. The partial substitutions T3 and T4 produced the best growth and yield for the chamomile plants.